1998
DOI: 10.1007/bf02904704
|View full text |Cite
|
Sign up to set email alerts
|

Role for glucose transporter 1 protein in human breast cancer

Abstract: Glycolysis is increased in cancer cells compared with normal cells. It has been shown that glucose enters cells via a family of five functional glucose transporters (GLUT). However, GLUT expression appears to be altered in human breast cancer, which may serve as a selective advantage and facilitate the metastatic potential of these cells. The relationship of GLUT isoform expression and breast cancer cell invasiveness has not been adequately addressed. Thus, the purpose of this study was to investigate whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 24 publications
5
90
1
Order By: Relevance
“…These observations are in agreement with the idea that MDA-MB-231 cells rely on aerobic glycolysis to fulfill their energetic demands, while MCF-7 cells utilize OXPHOS (Guppy et al 2002). Here, it should be noted that, while we did not observe Glut-1 expression in MCF-7 cells, other investigators reported that MCF-7 cells did express Glut-1, even though the expression was greatly reduced compared to MDA-MB-231 cells (Grover-McKay et al 1998).…”
Section: Inhibition Of Hsp90 and Proteasomesupporting
confidence: 75%
“…These observations are in agreement with the idea that MDA-MB-231 cells rely on aerobic glycolysis to fulfill their energetic demands, while MCF-7 cells utilize OXPHOS (Guppy et al 2002). Here, it should be noted that, while we did not observe Glut-1 expression in MCF-7 cells, other investigators reported that MCF-7 cells did express Glut-1, even though the expression was greatly reduced compared to MDA-MB-231 cells (Grover-McKay et al 1998).…”
Section: Inhibition Of Hsp90 and Proteasomesupporting
confidence: 75%
“…This has application in the clinic, where hypoxia driven changes in Glut-1 expression relates to the degree of malignant transformation and invasive portential of cervix metaplasia (Rudlowski et al, 2003), breast cancer (Gatenby et al, 2007) and hepatocellular carcinoma (Amann et al, 2009). Glut-1 expression correlates with tumor invasiveness (Grover-McKay et al, 1998) and promotes increased proliferative activity, which is associated with the loss of functional p53 (Schwartzenberg-Bar-Yoseph et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…GLUT1 is widely considered responsible for glucose transport in breast tissue [117][118][119][120]. Existence of GLUT2 in breast was controversial and no apparent difference was observed between normal and malignant tissues [117,118,121]. GLUT3, which is more likely expressed in the brain, was not detected in either normal or tumor breast tissues [118], except of breast cancer cell line ZR-75 [122].…”
Section: Augmented Glucose Uptakementioning
confidence: 99%
“…GLUT3, which is more likely expressed in the brain, was not detected in either normal or tumor breast tissues [118], except of breast cancer cell line ZR-75 [122]. The expression of GLUT4 was found in various human malignant breast tissues, but not in human breast cancer cell lines -MCF-7, MDA-MB-435 and MDA-MB-23 [117,118,121]. The high-affinity fructose transporter GLUT5 was selectively expressed in human breast cancer tissues, indicating that fructose may be a good energy substrate in tumor cells [116,119].…”
Section: Augmented Glucose Uptakementioning
confidence: 99%
See 1 more Smart Citation